The social media MBA : your competitive edge in social media strategy development & delivery - Holloman, Christer, 1980-; Adeyeri, Eb (Wiley, 2012)
"It's a fact that companies so far have only scratched the surface of what can be achieved with social media. Whatever continent, industry, company size, current degree of social media adoption or your job title, the purpose of this book is to inspire you to see how you can raise the bar further to reap new rewards. It will give you the tools to make a difference to your organisation's social media strategy development and delivery going forward. In addition it will also give you more intellectual support and confidence to discuss social media on a higher level with peers, inspire colleagues or negotiate and create support for increased investments from your leadership team. In The Social Media MBA editor Christer Holloman has crowd sourced 15 thought leaders from 4 continents to offer an exceptional educational programme written for experienced social media professionals just like you. In addition, learn through cases studies produced by the social leaders at these brands: ARM by Kerry McGuire Balanza, Director of Strategic Marketing; Aviva by Jan Gooding, Global Brand Director; Dell by Stuart Handley, Communications Director; Evans Cycles by Will Lockie, Head of Social Media; GlaxoSmithKlein (Ribena) by Verity Clifton, Brand Marketing Manager; Kodak by Madlen Nicolaus, Social Media Manager; Phillips by Hans Notenboom, Global Director B2B Online; Sage by Cath Sheldon, Online PR Specialist. There is more, connect with the co-authors and other readers by joining The Social Media MBA Alumi group, visit http://www.socialmedia-mba.com or search or the group on LinkedIn to stay updated on the latest, ask questions or join the discussions"--Vydavatelská anotace
Obsahuje rejstřík
Keywords: sociální média; sociální sítě; internetový marketing; řízení vztahů se zákazníky; strategický management; social media; social networks; Internet marketing; customer relationship management; strategic planning; případové studie; case studies